Understanding forensic DNA - Bell, Suzanne 1959-; Butler, John M. 1969- (Cambridge University Press, 2022)
Forensic DNA analysis plays a central role in the judicial system. A DNA sample can change the course of an investigation with immense consequences. Because DNA typing is recognized as the epitome of forensic science, increasing public awareness in this area is vital. Through several cases, examples and illustrations, this book explains the basic principles of forensic DNA typing, and how it integrates with law enforcement investigations and legal decisions. Written for a general readership, Understanding Forensic DNA explains both the power and the limitations of DNA analysis. This book dispels common misunderstandings regarding DNA analysis and shows how astounding match probabilities such as one-in-a-trillion are calculated, what they really mean, and why DNA alone never solves a case
Title from publisher's bibliographic system (viewed on 07 Sep 2022)
Biological Identification -- Before DNA -- First Generation Forensic DNA -- STR Methods and Loci -- DNA Analysis and Interpretation : Single-Source Samples and Simple Mixtures -- The Curse of Sensitivity -- From Mothers and Fathers -- Emerging Technologies -- Emerging Issues
Keywords: DNA fingerprinting; Forensic pathology